La construcción de identidades a través de los diálogos de saber del Círculo de Palabra de la Comunidad Muisca Chibcha de Bacatá (2018)
This article, a product of scientific research, aims to examine the different theoretical and methodological contributions of the Word Circle of the Muisca Chibcha Community of Bacatá in the construction of the different identities of its participants, with the aim of identifying those pedagogical elements used by the collectivity, both in the dialogues of knowledge and in the different dynamics that they carry out in this space. The research was developed from the ethnographic method, which made possible the detailed description of the situations, events, people, interactions and behaviors that were observable in the investigation; besides allowing, from the field work, the possibility of knowing and interacting with the grandparents, members of the Muisca Chibcha community of Bacatá and the other assistants to the Word Circle. Regarding the analysis of the results of this micro-ethnographic research, the concepts “Emic and Etic” were taken into account, where it is generally concluded that the Word Circle is a pedagogical tool and an intercultural exercise practice that has as purpose the construction of identity of people, the generation of spaces for dialogue between cultures, the strengthening of social ties and the construction of a better society based on respect for differences.